Evaluation of plant extracts against Fusarium oxysporum, wilt pathogen of fenugreek - RAJESH KUMAR GUPTA, R.K. BANSAL and (Indian Phytopathology, 2002)
The efficacy of leaf extracts of Azadirachta indica, Atropa belladonna, Calotropis procera, Ocimum basilicum, Eucalyptus amygdalina, Ailanthus excelsa and Lantana camara against the fenugreek wilt pathogen Fusarium oxysporum was tested in vitro. Each extract was tested at 5 different concentrations: 20, 40, 60, 80 and 100% using the poisoned food technique. Among the 7 leaf extracts, A. indica was highly toxic to F. oxysporum showing complete inhibition of mycelial growth and spore germination at 100% concentration. O. basilicum and L. camara also inhibited mycelial growth and spore germination at all 5 concentrations although they did not exhibit complete inhibition even at 100% concentration. A. belladonna and E. amygdalina were least effective.